Results after implementation of the European protocol in the management of post-TAVI conduction disorders - Domingo López Vázquez; Xacobe Flores Ríos; Fausto de Andrés; Carmen Vidau Getán; Ramón Calviño Santos; José Manuel Vázquez Rodríguez (REC: Interventional Cardiology (English Ed.))
To the Editor, Currently, transcatheter aortic valve implantation (TAVI) is the treatment of choice for most patients with severe aortic stenosis. Due to the anatomical proximity of the conduction system to the aortic valve, the development of cardiac conduction disorders is a common finding after the procedure, being the most severe complete atrioventricular block (CAVB) and the most common left bundle branch block (LBBB), with incidence rates from 4% up to 60%.1 The latter has been associated with a worse prognosis in observational studies.2 Based on this, European scientific societies have developed a protocol for the management of post-TAVI conduction disorders.3 However, the clinical utility of the practical implementation of this protocol has not been evaluated to date. We conducted a retrospective analysis with 337 patients treated with TAVI at our center from September 2021—when the European clinical practice guidelines algorithm for post-TAVI conduction disorders was systematically implemented—through March 2023. We recorded the rate of conduction disorders, their management, and, in cases where a pacemaker was implanted, the rate of ventricular pacing 30 days after implantation. Continuous variables are expressed as mean and standard deviation, and the qualitative ones as proportions. Regarding inter-group differences, the Kaplan-Meier method was used to construct survival curves...